Новые виды орехотворок (Hymenoptera, Cynipidae) из Грузинской ССР - Дьякончук, Л.А. (Вестник зоологии, 1984)
New Species of Cynipidae (Hymenoptera) from Georgian SSR. Diakontshuk L. A.—
Vestn. zool., 1984, No. 3. Two Eryngium-dwelling species are described as new. Phanacis
(Pseudophanacis) eryngi sp. n. is distinct by 12-segment antennae and dilated 3rd sub-
costal vein sector. Aulacidea parvula sp. n. differs from all known species of the genus
by smaller body size, triangular radial cell of the forewing and by absent cubital vein Ist
sector. Type material is deposited in the Cynipidae collection, I. I. Schmalhausen Institute
of Zoology, Ukr. SSR Academy of Sciences (Kiev).